The effect of academic and pedagogic competences on basic teaching skills of mathematics teacher candidates in micro teaching - Kurnia Putri Sepdikasari Dirgantoro (Math Didactic: Jurnal Pendidikan Matematika, 2019)
Teaching skills are one of the basic skills that must be mastered by a teacher. Therefore, student teacher need to continuously train themselves to develop their teaching skills. One way that is attempted is through micro teaching in the PSAL (Planning, Strategy, Assessment, Learning) Mathematics course. The purpose of this study was to determine the contribution of the academic and pedagogic competences of student teacher to the basic skills of teaching them in micro teaching. The research subjects are 56 students of University of Pelita Harapan Mathematics Education Study Program class of 2017. This study is a correlational study and simple linear regression analysis. The instruments used in data collection include the rubric of micro teaching, archives of student score, and questionnaires. The results of this study are: (1) there is a significant correlation between academic abilities and basic teaching skills; (2) there is a significant effect of academic ability on basic teaching skills; (3) there is a significant correlation between pedagogic abilities and basic teaching skills; and (4) there is a significant effect of pedagogic skills on basic teaching skills. The conclusion is pedagogic and basic mathematics courses already in accordance with the needs of students.